Answer:
The answer is 1/(x+1)(x+y)
Explanation:
Given the equation
x-y/x²-1 × x-1/x²-y²
We will apply the difference of two square to solve the equation. According to the rule, if a and b are real numbers;
a²-b² = (a+b)(a-b)
Therefore x²-1 = x²-1² = (x+1)(x-1)
Similarly, x²-y² = (x+y)(x-y)
Substituting this functions in the question we have;
x-y/x²-1 × x-1/x²-y²
= x-y/(x+1)(x-1) × x-1/(x+y)(x-y)
x-y will cancel x-y and x-1 will also cancel out x-1 to reduce the equation to;
x-y/x²-1 × x-1/x²-y² = 1/x+1 × 1/x+y
= 1/(x+1)(x+y) which is the simplified form of the equation